In vitro investigations into the use of antimicrobials in combination to maintain efficacy of fluoroquinolones in poultry. (October 2016) - Randall, Luke; Ridley, Anne; Lemma, Fabrizio; Hale, Carol; Davies, Rob
Abstract: The aim of this study was to determine if apramycin, colistin or lincomycin–spectinomycin, in combination with enrofloxacin, was able prevent the emergence of mutants with reduced susceptibility to fluoroquinolone antibiotics in vitro . MICs were determined for enrofloxacin alone and in combination for panels of Campylobacter ( n  = 37), Escherichia coli ( n  = 52) and Salmonella (n = 52) isolates. MIC results suggested that apramycin, colistin and lincomycin–spectinomycin worked in an additive/indifferent way when each was combined with enrofloxacin. Apramycin was considered the most promising antibiotic for combination-therapy in conjunction with enrofloxacin, and further evaluations (MBCs, MPCs and time-kill-curves) were performed for this combination for selected isolates. Results suggest combination-therapy of enrofloxacin with apramycin increases the efficacy, as well as decreasing the emergence and survival of bacteria with mutational resistance to fluoroquinolone antibiotics. Such combination-therapy, minimising the development of mutational resistance, may have relevance for Campylobacter, E. coli and Salmonella infections in poultry. Highlights: Combination antibiotic therapy for treatment of poultry was investigated in-vitro . Combinations were enrofloxacin with apramycin, colistin or lincomycin–spectinomycin. Target bacteria were Campylobacter, Escherichia coli and Salmonella . Enrofloxacin and apramycin were considered the most suitable combinations.